Farming under fire: The interplay of armed conflict and climate-induced weather disruptions in agricultural input use - Ayalew, Hailemariam; Berhane, Guush; Wondale, Meseret; Breisinger, Clemens (International Food Policy Research Institute, 2024)
The recent surge in violent conflicts, intertwined with climate-induced drought risks, is jeopardizing decades of development progress in many low- and middle-income countries. This study investigates the compounded effects of armed conflicts and climate-induced disruptions on agricultural input use in Ethiopia, a country experiencing significant fragility due to both factors. Using a unique household- and plot-level panel dataset collected before (2019) and after (2023) the onset of a widespread conflict, we examine how these disruptions affect the use of key agricultural inputs, such as inorganic fertilizers, improved seeds, agrochemicals, compost, and manure. The analysis reveals that exposure to conflict significantly reduces the likelihood of using both inorganic and organic inputs. Conflict-affected households are 9 percentage points less likely to use both inorganic fertilizers and improved seeds, and 14 percentage points less likely to use organic fertilizers, such as compost and manure. Exposure to recurrent rainfall variability by inducing uncertainty of use of inputs further exacerbates these negative impacts, reducing fertilizer use by an additional 3 percent among drought-exposed households. These findings highlight the multifaceted challenges faced by smallholder farmers in fragile settings, where both conflict and environmental stressors undermine agricultural productivity and threaten food security. The study underscores the need for targeted anticipatory (pre-conflict) and resilience building (post-conflict) interventions to support resilience in agricultural practices within conflict-affected regions, particularly those facing climate-induced weather risks.